Oceans justice: Trade-offs between Sustainable Development Goals in the Seychelles. (January 2023) - Baker, Susan; Constant, Natasha; Nicol, Poppy
Abstract: The marine environment represents an important resource for the promotion of sustainable development. The Sustainable Development Goal (SDG) 14, Life Below Water, highlights the need to balance the economic, social, and environmental dimensions when using the World's oceans. However, trade-offs arise between the implementation of SDG goals and the well-being of different groups of people. The use of justice mechanisms is critical for achieving social equity outcomes from ocean use. Trade-offs in implementation between SDG14 and other SDGs in the Seychelles are examined through the lens of distributive and procedural justice. Content analysis of grey and policy literature and qualitative data derived from stakeholder workshops and focus group discussions are used to examine trade-offs between expanding marine protection through the Blue Economy initiative and Marine Spatial Planning (MSP), and the livelihoods and well-being of artisanal fishers. MSP limit fishers' access to marine resources through spatial, temporal, and permanent prohibitions on access to key fishing areas and gear use that negatively impact upon food security, subsistence livelihoods and well-being. These trade-offs reduce capacity to attain other SDG goals linked to alleviating poverty, hunger and good health and well-being. Consultation processes, by not giving adequate voice to fishers concerns and local knowledge, raise issues of procedural fairness. Trade-offs are largely borne by weaker socio-economic groups, leading to a failure to address issues of distributive fairness. Our research shows that the promotion of sustainable futures in the Seychelles remains elusive unless matters in relation to distributive justice are addressed and procedural fairness is provided. How justice mechanisms can be used in pursuit of social equity from ocean use is explained, and avenues for further research outlined. Highlights: Trade-offs between SDGs can undermine the international framework for sustainable development. The role of justice mechanisms in the promotion of social equity from ocean use is detailed. The lens of procedural justice helps understand how trade-offs between SDGs are made and by whom. The lens of distributive justice highlights how trade-offs decisions impact upon different social groups. The Blue Economy and MSP impact negatively upon artisanal fishers in the Seychelles bringing trade-offs between SDGs. Achieving SDGs and its social equity outcomes requires attention to justice mechanisms in decision making.